Mesoporous germanium nanoparticles synthesized in molten zinc chloride at low temperature as a high-performance anode for lithium-ion batteries. Issue 22 (17th May 2018) - Liu, Xianyu; Lin, Ning; Cai, Wenlong; Zhao, Yingyue; Zhou, Jianbin; Liang, Jianwen; Zhu, Yongchun; Qian, Yitai
Abstract : The mesoporous germanium nanoparticles are prepared by a "metathesis" reaction of magnesium germanide (Mg2 Ge) and zinc chloride (ZnCl2 ), and they exhibit excellent electrochemical performance for Li-ion batteries. Abstract : In a simple and convenient way, mesoporous germanium nanoparticles (mp-Ge NPs) are prepared by a "metathesis" reaction of magnesium germanide (Mg2 Ge) and zinc chloride (ZnCl2 ) in an autoclave at 300 °C. Investigated as anode materials for lithium-ion batteries, the prepared mp-Ge NPs exhibit a high capacity retention of 1048 mA h g −1 at 1 C after 1000 cycles and a high rate capacity of 727.1 mA h g −1 at 10 C in Li–Ge half cells. Additionally, a 3.4 V lithium-ion full cell (Ge-LiCoO2 ) with an energy retention of 85% (∼268.8 W h kg −1 ) over 100 cycles is achieved.